Speculative trade under unawareness: The infinite case - Martin Meier; Burkhard C. Schipper (University of California, Department of Economics, 2013)
We prove a no-speculative-trade theorem under unawareness for the infinite case. This generalizes the result for the finite case by Heifetz, Meier, and Schipper (2013).
Keywords: C70; C72; D53; D80; D82; D84; 330; awareness; unawareness; speculation; trade; agreement; common prior; common certainty